2019 AHA/ACC/HRS Focused Update of the 2014 AHA/ACC/HRS Guideline for the Management of Patients With Atrial Fibrillation: A Report of the American College of Cardiology/American Heart Association Task Force on Clinical Practice Guidelines and the Heart Rhythm Society in Collaboration With the Society of Thoracic Surgeons. Issue 2 (9th July 2019) - January, Craig T.; Wann, L. Samuel; Calkins, Hugh; Chen, Lin Y.; Cigarroa, Joaquin E.; Cleveland, Joseph C.; Ellinor, Patrick T.; Ezekowitz, Michael D.; Field, Michael E.; Furie, Karen L.; Heidenreich, Paul A.; Murray, Katherine T.; et al.
Abstract : Supplemental Digital Content is available in the text.